2006
DOI: 10.1016/j.micinf.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

CRM1, an RNA transporter, is a major species-specific restriction factor of human T cell leukemia virus type 1 (HTLV-1) in rat cells

Abstract: Rat ortholog of human CRM1 has been found to be responsible for the poor activity of viral Rex protein, which is essential for RNA export of human T cell leukemia virus type 1 (HTLV-1). Here, we examined species-specific barrier of HTLV-1 by establishing rat cell lines, including both adherent and CD4 + T cells, which express human CRM1 at physiological levels. We demonstrated that expression of human CRM1 in rat cells is not harmful to cell growth and is sufficient to restore the synthesis of the viral struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We also demonstrated hCRM1 expression in all Tg ratderived cell lines, which will be useful for the functional analysis of hCRM1 in HTLV-1-infected cells. We have previously reported that expression of hCRM1 induced an increase in HTLV-1 Gag production in both rat epithelial and T cells (21,69). Our present study also showed that T-cell lines established from hCRM1-Tg rats produced significantly greater amounts of p19 than cell lines established from Wt rats, further indicating the positive effect of hCRM1 on viral protein synthesis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We also demonstrated hCRM1 expression in all Tg ratderived cell lines, which will be useful for the functional analysis of hCRM1 in HTLV-1-infected cells. We have previously reported that expression of hCRM1 induced an increase in HTLV-1 Gag production in both rat epithelial and T cells (21,69). Our present study also showed that T-cell lines established from hCRM1-Tg rats produced significantly greater amounts of p19 than cell lines established from Wt rats, further indicating the positive effect of hCRM1 on viral protein synthesis.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously examined the differences in the pattern of viral gene expression between human and rat T cells infected with HTLV-1 (69). In rat cells, the levels of viral mRNAs encoding the Gag and Env proteins were much lower than those encoding the Tax and Rex proteins (36).…”
Section: Human T-cell Leukemia Virus Type 1 (Htlv-1) Is the Etiologicmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we identified CRM1, a cellular cofactor of Rex that exports viral mRNA from the nucleus to the cytoplasm, to be a major factor, which restricts efficient replication of HTLV-1 in rats [17][18][19]. Human CRM1 (hCRM1) transgenic (Tg) rat supports replication of HTLV-1 in T cells at the level similar to human T cells ex vivo [20].…”
mentioning
confidence: 99%